Efficient crop residue management under conservation agriculture for improving soil quality: A review - SAIRAM, MASINA; MAITRA, SAGAR; RAGHAVA, CHABOLU VENKATA; KRISHNA, TADIBOINA GOPALA; GAIKWAD, DINKAR J.; SAHOO, UPASANA; RAY, SUMIT (Farming & Management, 2023)
The intensification of cropping system is mandatory for a populus country like India. However, the enhancement of the cropping intensity simultaneously generates a huge quantity of crop residues. Presently, improper management of crop residues as well as in-situ burning of the same has become a prominent issue for adversely affecting the environment and loosing valuable plant nutrients. The conservation agriculture (CA) has shown a proven path where crop residues can be effectively utilized for improvement of the soil quality. Based on the above facts, an initiative has been taken to focus on efficient use of crop residues for improving soil quality vis-à-vis soil health. There are versatile uses of crop residues, however, they are equally potential in advancement of soil health. One of the main principles of CA is the inclusion of crop residues on the crop field as soil cover along with crop diversification and minimal soil disturbance. The inclusion of crop residues is potentially important for the improvement of physical, chemical and biological properties of the soil. Moreover, after decomposition, they add nutrients to the soil leading to enhanced soil fertility and crop productivity. Long-term application of crop residues under CA practices, more particularly with reduced and zero tillage, has been identified as an approach to increase soil productivity, increase the C-pool and promote the improved agroecosystem. The review article has focused on the inclusion of crop residues on improvement of soil physical, chemical and biological properties.